Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P; Ruiz-Fons, F; Vicente, J; Reyes-García, a. R; Alzaga, V; Gortázar, C (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Estimating red deer abundance in a wide range of management situations in Mediterranean habitats - Acevedo, P.; Ruiz-Fons, F.; Vicente, J.; Reyes-García, a R.; Alzaga, V.; Gortázar, C. (Journal of Zoology, 2008)
When human interventions interfere with the natural regulation of wildlife populations by favouring some species, overabundance can emerge. We evaluated different methods of estimating red deer abundance in a wide range of population densities from southern Spain. Distance sampling estimates were used as the reference method across 22 localities and were compared with two kilometric abundance indices (KAIs), four indices based on pellet group counts and two browsing indices (BWIs). The average red deer density estimated by distance sampling was 19.51 3.19 deer per 100 ha, showing a wide range across the study area (0.04–66.77). Distance sampling estimates correlated with the KAIs, pellet group-based index and the BWI. The agreement with distance sampling improved when groups were used instead of individuals in the KAIs, when the minimum pellet group size was ﬁxed at 20 pellets in the dropping counts, and when only highly palatable species were used in the BWI. Thus, several direct and indirect methods can estimate red deer abundance in Mediterranean habitats from Southern Spain with appropriate modiﬁcations.
Keywords: deer management; direct and indirect methods; Mediterranean area; overabundance; population abundance; red deer; ungulates

Herbivory in a Mediterranean forest: browsing impact and plant compensation - Focardi, Stefano; Tinelli, Aleandro (Acta Oecologica, 2005)
The compensatory response of plants to defoliation is likely to have important effects on plant–ungulate equilibria in forested ecosystems. We investigated the responses of six species of Mediterranean bushes to defoliation by wild ungulates, comparing an index of browsing impact with the productivity of plants in both open and exclusion plots. The data revealed a great diversity of plant responses to herbivory: Rubus ulmifolius was able to over-compensate and replace the lost tissues. Phillyrea latifolia exhibited a similar, albeit less evident, pattern, while Cistus salvifolius was severely damaged by browsing. Other species, such as Quercus ilex, Juncus acutus and Erica arborea, were not attacked to a large extent and suffered little or no harm. The results strongly suggest that Mediterranean ecosystems may tolerate large stocking rates of ungulates. However, the reduction of plant biomass due to browsing was very different in the six studied species, suggesting that when herbivory becomes severe the structure of the ecosystem will change with the more tolerant plants becoming more abundant. We can apply these results to improve management and conservation of relict coastal forests in the Mediterranean basin which are usually of small size and where decision-makers have to compromise between the conservation of plants and that of large mammals.
Keywords: Browsing; mediterranean environment; plant compensation; Relative growth rate; ungulates

Herbivory in a Mediterranean forest: browsing impact and plant compensation - Focardi, Stefano; Tinelli, Aleandro (Acta Oecologica, 2005)
The compensatory response of plants to defoliation is likely to have important effects on plant–ungulate equilibria in forested ecosystems. We investigated the responses of six species of Mediterranean bushes to defoliation by wild ungulates, comparing an index of browsing impact with the productivity of plants in both open and exclusion plots. The data revealed a great diversity of plant responses to herbivory: Rubus ulmifolius was able to over-compensate and replace the lost tissues. Phillyrea latifolia exhibited a similar, albeit less evident, pattern, while Cistus salvifolius was severely damaged by browsing. Other species, such as Quercus ilex, Juncus acutus and Erica arborea, were not attacked to a large extent and suffered little or no harm. The results strongly suggest that Mediterranean ecosystems may tolerate large stocking rates of ungulates. However, the reduction of plant biomass due to browsing was very different in the six studied species, suggesting that when herbivory becomes severe the structure of the ecosystem will change with the more tolerant plants becoming more abundant. We can apply these results to improve management and conservation of relict coastal forests in the Mediterranean basin which are usually of small size and where decision-makers have to compromise between the conservation of plants and that of large mammals.
Keywords: Browsing; mediterranean environment; plant compensation; Relative growth rate; ungulates

HABITAT PREFERENCE OF SPANISH IBEX AND OTHER UNGULATES IN SIERRAS DE CAZORLA Y SEGURA (SPAIN) - ESCOS, J.; Alados, C. L. (MAMMALIA, 1992)
Studied the habitat preference in Autumn and Spring periods of Spanish ibex (Capra pyrenaica), fallow deer (Dama dama) and red deer (Cervus elaphus) in the Sierras de Cazorla y Segura Park (Spain). Spanish ibex occupied most altitude range studied, especially highest parts and avoiding areas below 800 m, red deer selected lowest elevations between 700 to 1100 m and fallow deer (between 1200-1600 m) occupied an intermediate annual altitudinal range. All the ungulates studied showed, except the red deer populations, a descent of altitudinal levels in the Spring period. Ibex used more covered areas specially females and young in Spring period, fallow deer occupied open habitats and red deer preferred holm-oak woods. In general terms the rut occurred in more open areas while in the birth season, females and young especially occupied covered areas. According to the overlap index (Pianka 1973) ibex with fallow deer could get a high risk of competition, while Spanish ibex and red deer, the only endemic species show the lowest level of overlapping on the resources studied. Segregation of the sexes studied in different habitats was observed. In Autumn, Spanish ibex and fallow deer showed a tendency to occupy sunny areas at dawn and dusk and this tendency occurred in red deer only at dawn but not at dusk. However in Spring, Spanish ibex, fallow and red deer occupied sunny slopes at dusk but only fallow deer do so at dawn.
The following values have no corresponding Zotero field: pub-location: 55 RUE DE BUFFON, 75005 PARIS, FRANCE publisher: MUSEUM NAT HIST NATURELLE
Keywords: APS; Capra pyrenaica; cervus elaphus; Dama dama; habitat prefference; Holm oak; Spain; ungulates